KAJIAN STRUKTURAL CERPEN WA KĀNAT AD-DUNYĀ DALAM ANTOLOGI CERPEN ARINILLĀH KARYA TAUFIQ EL-HAKIM - Arief Fiddienika; Fatkhul Ulum; Rachmat Nuhidayatullah (Universitas Negeri Makassar, 2023)
Structural Analysis of the Short Story of Wa Kānat Ad-Dunyā in the Anthology of the Short Story of Arinillāh by Taufiq El-Hakim. The purpose of this study is to describe: (1) intrinsic elements, (2) the relationship between elements, and (3) educational values in the short story wa kānat ad-dunyaā by Taufiq El-Hakim. This research is literary research with a text translation approach and structural theory. The data in the form of a short story